UPAYA MENGATASI ISLAMOPHOBIA DI INDONESIA MELALUI PENDIDIKAN SPIRITUAL (Iceberg and U-Theory Analisyst) - Muhammad Rifqi Zam Zami; Muhammad Hafizh; Dinda Helmi Kayana Juwita (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study explores the gap between the ideals and practical application of spiritual education, focusing on persistent Islamophobia in Indonesia. Ideally, spiritual education fosters tolerance and humanism, accommodating diverse religious expressions like the niqab, burqa, cingkrang pants, and full beards, aligned with Islam’s principles. However, ongoing Islamophobia reveals significant flaws in its implementation. This qualitative literature review synthesizes primary and secondary data from scholarly works over the past decade, using Iceberg and U-Theory methods within a phenomenological framework. The study aims to identify spiritual concepts that mitigate Islamophobia, especially post-2002 Bali terrorism. Findings show that enhancing spiritual education and promoting religious moderation are crucial for reducing Islamophobia by providing accurate understandings of Islamic teachings. Misinterpretations and extremist ideologies, rather than Islam's core tenets, are the root causes of Islamophobic sentiments